Sales Management Support and Analytics untuk Meningkatkan Koordinasi Pekerja dan Pelayanan Pembeli UD. XYZ - Melissa Marvella; Leo Willyanto Santoso; Yulia Yulia (Universitas Kristen Petra, 2022)
UD. XYZ is a business that sells products with a wholesale preorder system. The products offered are handicrafts such as of invitations and souvenirs. In running a business, especially in order processing, each salesperson is tasked with interacting with the customers. This causes customers to have a different contact numbers regarding UD. XYZ. Matter of separate information, it becomes difficult to track orders. The method used in charge on designing information system is the V-Shaped Model. The VShaped Model method is one of the SDLC (System Development Life Cycle) models. Meanwhile, the testing method used is White box testing and User Experience Questionnaire (UEQ). Based on the research that has been done, white box testing the results are 98.5%. On the other hand, the User Experience Questionnaire (UEQ) based on 6 UEQ scales resulted in 5 categories above the average and 1 category with good scores.